Imidazo[1,2-a]pyridine Scaffold as Prospective Therapeutic Agents - Deep, Aakash; Kaur Bhatia, Richa; Kaur, Ramanjot; Kumar, Sanjiv; Kumar Jain, Upendra; Singh, Harinder; Batra, Sandeep; Kaushik, Dinesh; Kishore Deb, Pran (Current Topics in Medicinal Chemistry, 2017)
Imidazo[1,2-a]pyridine is one of the most potential bicyclic 5–6 heterocyclic rings that is recognized as a “drug prejudice” scaffold due to its broad range of applications in medicinal chemistry such as anticancer, antimycobacterial, antileishmanial, anticonvulsant, antimicrobial, antiviral, antidiabetic, proton pump inhibitor, insecticidal activities. This scaffold has also been represented in various marketed preparations such as zolimidine, zolpidem, alpidem. Therefore, several attempts were made to carry out the structural modifications of this scaffold to discover and develop novel therapeutic agents. This review provides a valuable insight into the research findings of wide range of derivatives of imidazo[1,2-a]pyridine scaffold leading to promising heterocyclic compounds which could be explored further for the synthesis of new derivatives as well as construction of potential drug-like chemical libraries for biological screening in search of new therapeutic agents.
Keywords: Antiviral